Validation of analytical method for determination of microbiological quality of antifungal shampoo containing 2% ketoconazole: Enumeration test and tests for specified microorganisms (Method suitability test) - Nadica Gjurichikj; Julija Gjorchevska Aceska; Maja Veljanovska Todorovska; Tatjana Gjurichikj; Liljana Anastasova; Rumenka Petkovska (Makedonsko Farmacevtski Bilten)
Microbiological quality screening of non - sterile product is conducted by suitable enumeration tests and tests for absence of specified microorganisms. The European Pharmacopoeia offers several methods for conducting these tests. The suitability of a compendial microbiological method must be demonstrated to ensure accuracy and reliability of test results. The work presented here had the purpose of creating a validated and reliable method for screening the microbiological quality of antifungal shampoo containing 2% ketoconazole. Method suitability tests for the parameters: Total aerobic microbial count (TAMC), Total yeast and mold count (TYMC), absence of Staphylococcus aureus and Pseudomonas aeruginosa were determined according to chapters 2.6.12. Microbial examination of non – sterile products: microbial enumeration tests and 2.6.13. Microbial examination of non – sterile products: test for specified microorganisms. The membrane filtration method was chosen for TAMC and TYMC. The criteria for method suitability of the counting methods TAMC and TYMC – a mean count of each of the microorganisms differing by a factor not greater than 2 from the value of the control in the absence of the product (recovery rate 50% - 150% of the test group with product in comparison with the positive control group) was obtained. The criteria of growth on selective media for P. aeruginosa and S. aureus were also obtained.